“Diseño de un Sistema de Producción de CO2 para Consumo Humano a partir de las emisiones Generadas en un Relleno Sanitario” - Roldan Heivis, Quispe Solano (2019)
This project aims to demonstrate that the emissions generated in a landfill polluting the environment, can be exploited to obtain highly pure CO2 for human consumption in quantities sufficient to cover part of the growing market demand for increasingly demanding, an issue currently is being increasingly critical generation of emissions on the planet causing global warming. To reach the objective, design a recovery system for capturing and gases emitted by the reaction and decomposition of solid waste to produce high purity CO2 for human consumption in order to optimize the conditions of the place. The gases will be captured in a storage tank being cooled to room temperature, then be burned with ambient air, purified, compressed, dried, liquefied and stored. The CO2 obtained will be analyzed to determine the purity of CO2 and other gases (O2, N2, Stotal, C2H4O, CO, volatile hydrocarbons such as methane, odor, taste and appearance in water).